Probing the temporal and spatial variations of dust emission in the protoplanetary disk of DG Tau with VLTI/MIDI: Preliminary results. Issue 9 (November 2013) - Gabányi, K. É.; Mosoni, L.; Juhász, A.; Ábrahám, P.; Ratzka, Th.; Sipos, N.; van Boekel, R.; Jaffe, W.; Barnaföldi, Gergely Gábor; Forgás‐Dajka, Emese; Kiss, Csaba; Verebélyi, Erika
Abstract The signatures of dust processing and grain growth – related to the formation of rocky planets – are easily seen in midinfrared spectral features. One important diagnostic tool in this context is the silicate feature in the spectra of young stellar objects (YSO). The low‐mass YSO, DG Tau shows unique temporal variations in its silicate feature. We conducted multi‐epoch observations of DG Tau with the MID‐Infrared Interferometric instrument of the Very Large Telescope Interferometer to obtain the spectra of the inner and outer disk regions in order to investigate where the previously reported variations of the silicate feature originate from. Here we present the preliminary results of the first two epochs of observations. We found that on a time‐scale of two months, the source showed significant brightening. At the same time the mid‐infrared emitting region expanded. While the identification of the silicate feature is difficult, our results qualitatively agree with the scenario explaining the varying silicate feature with dust lifted up above the disk. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)